KEPRAKTISAN DAN EFEKTIVITAS LKPD BERBASIS PROBLEM BASED LEARNING BERKONTEKS PESISIR PANTAI UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK - Dini Lianda Afrelica; Effie Efrida Muchlis; Agus Susanta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the practicality and effectiveness of a Problem Based Learning (PBL)-based Student Worksheet (LKPD) within a coastal context on the topic of relations and functions to improve the mathematical problem-solving abilities of eighth-grade students at SMP Negeri 7 Kota Bengkulu. The study employs the Plomp development model, which consists of three stages: preliminary investigation, prototyping, and assessment. Practicality was measured through a small group test involving six students using the USE Questionnaire. Practicality results showed average scores of 4.25 for usefulness (very practical), 4.08 for ease of use (practical), 4.29 for ease of learning (very practical), and 4.17 for satisfaction (practical). Effectiveness was measured through classical completeness, N-gain score, and the Wilcoxon test. Effectiveness results revealed classical completeness of 80%, exceeding the minimum criterion of 60%, an N-gain score of 0.77 (high category), and a Wilcoxon significance value of 0.000 < 0.05. These findings demonstrate that the coastal-context PBL-based LKPD significantly improves students' mathematical problem-solving abilities.